Cystatin A suppresses tumor cell growth through inhibiting epithelial to mesenchymal transition in human lung cancer - Ma, Yunxia (Oncotarget, 2017)
Cystatin A (CSTA), belonging to type 1 cystatin super-family, is expressed primarily in epithelial and lymphoid tissues for protecting cells from proteolysis of cytoplasmic and cytoskeletal proteins by cathepsins B, H and L. CSTA acts as a tumor suppressor in esophageal cancer, however, its role in lung cancer has not yet been elucidated. Here we found that CSTA was down-regulated in all lung cancer cell lines compared to normal lung epithelial cells. CSTA was restored in most lung cancer cell lines after treatment with demethylation agent 5-aza-2-deoxycytidine and deacetylation agent Trichostatin. Bisulfite sequencing revealed that CSTA was partially methylated in the promoter and exon 1. In primary lung tumors, squamous cell carcinoma (SCC) significantly expressed more CSTA compared to adenocarcinoma (p<0.00001), and higher expression of CSTA was significantly associated with lower tumor grade (p<0.01). CSTA stable transfection reduced the activity of cathepsin B and inhibited the ability of colony formation, migration and invasion, and enhanced gemcitabine-induced apoptosis. CSTA overexpression resulted in reduced activity of ERK, p-38, and AKT. Additionally, CSTA overexpression led to a mesenchymal to epithelial transition (MET) and prevented the TGF-β1-induced epithelial to mesenchymal transition (EMT) through inhibiting the ERK/MAPK pathway. In conclusion, our date indicate 1) epigenetic regulation is associated with CSTA gene silencing; 2) CSTA exerts tumor suppressive function through inhibiting MAPK and AKT pathways; 3) Overexpression of CSTA leads to MET and prevents TGF-β1-induced EMT by modulating the MAPK pathway; 4) CSTA may be a potential biomarker for lung SCC and tumor differentiation.